The native potato, a symbol of macho expression in the Quechua culture of Peru - Gutiérrez-Gómez, Edgar; Moscoso-Paucarchuco, Ketty Marilú; Luján-Pérez, Diana; Aspur-Barrientos, Jaime Carmelo; Quispe-Medina, Eugenia Rocío (Frontiers in Sociology, 2024)
The present field research focuses on the native potato varieties, Wira pasña and Llumchuy waqachi, cultivated in the Peruvian highlands at roughly 4,000 m above sea level. The objective is to analyze the macho essence of the names assigned to the native potato, names that represent the social manifestation of women in Quechua culture. Participant observation and interviews about the different daily activities of the participants facilitated the research on the macho essence of the names of the native potato in the Quechua culture. The preponderant Quechua oral sources in the Peruvian Andes did not allow us to identify exactly how names associated with the macho way of social life were assigned to the native potatoes.